Factors associated with a borderline personality disorder diagnosis in the emergency department - Artioli, Mariasole; Bougon, Emmanuelle; Mathur, Anjali; Salles, Juliette (Frontiers in Psychiatry, 2022)
Introduction: Research on borderline personality disorder (BPD) has shown that less intensive care is especially effective when patients have been told about their condition. However, problems with diagnosing the disorder are also described in the literature. This study thus aims to explore the factors associated with the challenges of identifying and then communicating a BPD diagnosis to patients. Methods: We analyzed a database of 202 patients of Toulouse University Hospital (France) who had a CIM -10 F60.3 diagnosis. This data was used to identify the sociodemographic and clinical benchmarks associated with patients who had received an established BPD diagnosis prior to their attendance at the hospital’s emergency department (ED) in the study period. Results: 63% of the patients admitted to our psychiatric ED had been given an earlier diagnosis of BPD. Those who had not been diagnosed were more likely to: not have undergone any psychiatric follow-up; not have been hospitalized in the psychiatry department; and not have previously attended at the ED. Patients with BPD and a comorbidity of MDD were also less likely to have received a BPD diagnosis before their ED admission. Conclusion: This study found that patients without an established BPD diagnosis who present at the ED are more likely to not be known to the psychiatric care system. This suggests that EDs have a specific role to play in making a diagnosis and the subsequent orientation of care.